Effects of land-use changes on city-level net carbon emissions based on a coupled model. Issue 3 (4th May 2017) - Fu, Bitian; Wu, Meng; Che, Yue; Yang, Kai
ABSTRACT: Shanghai is a rapidly developing metropolitan area and concentrations of greenhouse gases are high. Carbon-sink and carbon-source estimation are of significance for carbon-emissions reduction. This paper describes the effect of land-use change on the variation of urban net carbon emissions, and discusses the probable spatiotemporal impact on the dynamics of carbon emissions using coupled SD (system dynamics) and CLUE-S (the conversion of land use and its effects at small regional extent) models. The results show that: increase in construction land and decrease in agricultural land have positive and negative effects on land-use emissions, respectively; under the Basic Policy scenario, total net carbon emissions will continue to increase, from 39.43 to 80.28 Mt, with a decreasing growth rate; the increase/decrease in carbon emissions occurs mainly in urban–rural fringes and source water areas; the conversion of all land-use types to construction land is the main carbon source, while the conversion of agricultural land to ecological land is the main carbon sink. Two land-use strategies are suggested for the mitigation of carbon emissions in Shanghai. It is also shown that the coupled models are suitable for simulating and predicting spatiotemporal city-level net carbon emissions and are applicable to similar cities in developing countries.